Female Managers' Experiences of Work-family Enrichment Realization: A Grounded Theory Study - Sara Makipour; Abdollah Shafiabady; Mohammad Reza Falsafinejad; Anahita Khodabakhshi-koolaee (Iran University of Medical Sciences, 2021)
Background: Challenges created by the simultaneous management of family and work among working women, especially married female managers with children are serious issues affecting all human societies, including Iran. Accordingly, the present study aimed to explore the realization of work-family enrichment based on the experiences of married female managers working in Parsian Bank. Methods: This qualitative study was conducted using the grounded theory approach. The study participants were 22 female managers who were selected using purposive and theoretical sampling methods from the staff of Parsian Bank, in 2019. The necessary data were collected by semi-structured interviews. The collected data were analyzed using the three-step (open, axial, selective) coding procedure (Strauss & Corbin, 1998). The collected data were coded and categorized using the constant comparison method in MAXQDA. Results: The obtained results indicated that female managers employed several strategies, including instrumental strategies, problem-solving management strategies, emotion-related strategies, behavioral measures, and measures to improve personal development and growth for work-family enrichment. The factors facilitating work-family enrichment were self-efficacy, emotional intelligence, support, and environmental network. However, other factors, including socio-cultural characteristics, the challenges of family cultural context, the non-supportive culture of the organization, and the cultural challenges of society were barriers for work-family enrichment. This process led to job satisfaction and satisfaction with marital life among the examined female managers. The core variable manifested as "the multidimensional use of self to enrich work and family". Conclusion: The insights from this study added to the knowledge of work-family enrichment among female managers. Female managers and officials can use this model to better understand and manage family and work, concurrently.